Institutional Voids and Organization Studies: Towards an epistemological rupture. Issue 10 (October 2019) - Bothello, Joel; Nason, Robert S.; Schnyder, Gerhard
In this essay, we critique the usage of the term 'institutional void' to characterize non-Western contexts in organizational studies. We explore how 'conceptual stretching' of institutional voids – specifically, the theoretical and geographic expansion of the concept – has led not only to poor construct clarity, but also pejorative labelling of non-Western countries. We argue that research using this term perpetuates an ethnocentric bias by deifying market development and overlooking the richness and power of informal and non-market institutions in shaping local economic activity. We call for an 'epistemological rupture' to decolonize organizational scholarship in non-Western settings and facilitate contextually grounded research approaches that allow for more indigenous theorization.